Penelusuran Minat Dan Bakat Olahraga Pada Siswa Sekolah Menengah Pertama Di Kabupaten Jepara Tahun Pelajaran 2019/2020 (Universitas Negeri Semarang, 2020)
The background of this research is the unknown sporting talents of students, the suitability of student interests and talents, the lack of knowledge of physical education teachers about scouting for sports search talent methods, and coaching that is not yet optimal. The purpose of this study: to determine the sports talent of junior high school students in Jepara Regency in the academic year 2019/2020 and the suitability of students' interests. This research approach uses quantitative descriptive methods. The technique of collecting data uses: (1) The sport search talent test is used to find out the talents students have, (2) The interview is used to confirm the results of the sport search talent test. The population in this study were junior high school students in Jepara Regency. The sampling technique uses purposive sampling. Data analysis in this research uses descriptive presents. Data processing using the sport search software application. The results of data analysis, a total of 17 students 11.2% of test takers had an interest in accordance with their talents and 135 students or 88.8% of test takers had an interest that was not in accordance with their talents. The conclusion obtained is that junior high school students in Jepara Regency have a variety of sports talents, but some of the potential is not in accordance with the interests of students.. With this research, it is hoped that it will become a reference or alternative for the process of scouting and developing sports talent in Jepara Regency and other area.